2021
DOI: 10.1039/d0ra07035a
|View full text |Cite
|
Sign up to set email alerts
|

The inhibition of Mpro, the primary protease of COVID-19, byPoria cocosand its active compounds: a network pharmacology and molecular docking study

Abstract: The inhibition of Mpro, the primary protease of COVID-19, by Poria cocos.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…The results indicated that the analytical performance and sensitivity were comparable with conventional HPLC and HPLC-MS methods. 5,6 The detailed information is summarized in Table 1. In addition, as depicted in Table S3,† the testing stability was carried out, and the results showed good stability (RSD% < 5%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results indicated that the analytical performance and sensitivity were comparable with conventional HPLC and HPLC-MS methods. 5,6 The detailed information is summarized in Table 1. In addition, as depicted in Table S3,† the testing stability was carried out, and the results showed good stability (RSD% < 5%).…”
Section: Resultsmentioning
confidence: 99%
“…These parts have respective pharmacological functions. Poria cocos , also referred to as white Poria (WP, Baifuling), has numerous properties for treating tumors, 3 inflammation, 4 viral diseases, 5 etc. The epidermal part of Poria cocos , known as Poriae cutis (PC, Fulingpi), specializes in diuresis and detumescence.…”
Section: Introductionmentioning
confidence: 99%
“…PA has been further observed to decrease blood glucose levels in streptozocin-treated mice by enhancing insulin sensitivity irrespective of peroxisome proliferator-activated receptor-γ (69). I, PA displays inhibitory effects on the SARS-CoV-2 3CL hydrolytic enzyme in vitro, with an IC 50 value of 18.607 µM (12). Akihisa et al (17) demonstrated that PA exhibits antiviral activity against Epstein-Barr virus early antigen-induced TPA in Raji cells, with an IC 50 value of 286 mol ratio/32 pmol TPA.…”
Section: Pharmacological Activitiesmentioning
confidence: 99%
“…As presented in Table I , PA displays inhibitory effects on the SARS-CoV-2 3CL hydrolytic enzyme in vitro , with an IC 50 value of 18.607 µ M ( 12 ). Akihisa et al ( 17 ) demonstrated that PA exhibits antiviral activity against Epstein-Barr virus early antigen-induced TPA in Raji cells, with an IC 50 value of 286 mol ratio/32 pmol TPA.…”
Section: Pharmacological Activitiesmentioning
confidence: 99%
See 1 more Smart Citation